Surveillance of rotavirus diarrhea - Titis Widowati; Yati Soenarto; Achirul Bakrie; Hera Nirwati (Indonesian Pediatric Society, 2012)
Background Rotavirus is a major cause of severe diarrhea anddehydration in children worldwide. Data on the burden of diseasein Indonesia is limited.Objective To provide an epidemiological profile of rotavirusinfection among children hospitalized for diarrhea in MohammadHoesin Hospital, Palembang.Methods In January- December 2006, a prospective, hospitalbasedsurveillance was carried out in children aged less thanfive years, presenting with diarrhea. Stool samples wereexamined for rotavirus using enzyme immunoassay (EIA).G- and P-typing were performed on specimens confirmed tobe positive by EIA.Results A total of 513 fecal specimens from 534 children weretested for rotavirus. Rotavirus was detected in 64% of thespecimens, mostly of the G9 type (62.5%). Incidence ofrotavirusdiarrhea was highest in the 6 month to 2 years age group (60.4%).Children with rotavirus diarrhea were more likely to present withdehydration, compared to those with non-rotavirus diarrhea (94%vs 70%, respectively, P=0.03).Conclusion Rotavirus was the most common pathogen foundin children with diarrhea. Rotavirus was detected in 64% ofpediatric diarrheal specimens tested in our study. This findingwarrants the use of a large-scale program to prevent disease,such as vaccination against rotavirus. [Paediatr lndones.2012;52:22-7].